Evaluation of concentrations of pro/anti-inflammatory cytokines after complication-free ECRP in cholangiocarcinoma - Yıldız, Kemal; İnce, Ali Tüzün; Gangarapu, Venkatanarayana; Buğdacı, Mehmet Sait; Baysal, Birol; Kayar, Yusuf; Sarbay Kemik, Ahu; Şentürk, Hakan (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Variations in pro and anti-inflammatory cytokine levels occur commonly after ERCP procedure complications, such as in post-ERCP pancreatitis. Besides, the relationship between increased cytokine levels and multidrug resistance has been shown in cholangiocarcinoma patients. Our aim was to investigate the impact of cytokine level changes on treatment strategy after uncomplicated ERCP procedures in cholangiocarcinoma patients. Materials and Methods: Of 75 patients enrolled in this study, 25 were cholangiocarcinoma, and 50 were choledocholithiasis patients. Levels of serum IL-1β, IL-6, IL-8, IL-10, and TNF-α were evaluated 2 hours before and 12 hours after complication-free ERCP, and statistical analysis of the results was obtained; if p value <0.05, it was accepted as statistically significant. Results: There was no statistically significant difference in the distribution of age (23-87 years; range: 59.8±16.6), gender (37 males vs 38 females), and levels of pre- and post-ERCP serum IL-1β, IL-6, IL-8, IL-10, and TNF-α in both patient groups, despite the presence of some change in test means (p:0.179, 0.445, 0.522, 0.937, and 0.065, respectively). However, significantly decreased levels of TNF-α were observed in the benign group, when comparing pre- and post-ERCP period (p<0.05). Conclusion: Serum concentrations of IL-1β, IL-6, IL-8, IL-10, and TNF-α evaluated after complication-free ERCP performed in patients with cholangiocarcinoma do not cause any change in treatment planning that would affect multidrug resistance.